1991
DOI: 10.1007/bf00192280
|View full text |Cite
|
Sign up to set email alerts
|

Crop root system response to irrigation

Abstract: In the field, root systems develop in response to both endogenous plant design and soil environment. Downward penetration of root systems results primarily from the growth of monocot axes or of dicot taproots; root proliferation at a given depth results from the growth of laterals at that depth. Root length densities generally decline exponentially with depth under well-watered conditions. Root growth rates are partially controlled by soil conditions. Under irrigation, the most critical soil properties for roo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 46 publications
2
23
0
1
Order By: Relevance
“…Soil rhizosphere aeration status is an important aspect of soil quality and soil ecology, which has been paid to less attention to [1][2][3]. The condition of root growth is directly related to plant growth and development, whereas root environment and root respiration are important factors for the normal growth of the roots.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Soil rhizosphere aeration status is an important aspect of soil quality and soil ecology, which has been paid to less attention to [1][2][3]. The condition of root growth is directly related to plant growth and development, whereas root environment and root respiration are important factors for the normal growth of the roots.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, researchers are paying increasing attention to the provision of suitable environments (i.e., adequate water vapor) for the healthy growth of crops. Soil-root system is the most important aspect [1][2][3][4]. Excessive soil moisture and compaction can greatly inhibit the healthy growth of crops [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Soil physical properties of each soil type can be summarized as follows: haplic andosol had low soil penetrability, low bulk density and large gas volume; umbric andosol had low soil penetrability, low bulk density and small gas volume; and dystric cambisol had high soil penetrability, high bulk density and small gas volume. As Klepper (1991) and Tardieu (1994) reported that the penetration resistance of soils affects maximum rooting depth and vertical root distribution, differences in such soil physical properties might strongly infl uence the root system in each soil. Miyoshi (1972) reported for both volcanic ash soils and non-volcanic ash soils that if the soil density measured with a Yamanaka type soil hardness meter became greater than 22−23 mm (0.84−0.98 MPa), the root distribution rate in almost all crops, including wheat, declined rapidly.…”
Section: Discussionmentioning
confidence: 99%
“…Eissenstat 1991;Klepper 1991;Green and Clothier 1995). Herbaceous plants are also likely to evolve their root systems into subsoil layers (e.g.…”
Section: Introductionmentioning
confidence: 99%